In order to lower the antinutritional activity of serine protease inhibitors, we need to understand their role in seed development - Vorster, Juan; Westhuizen, Willem van der; Plessis, Gedion du; Marais, Diana; Sparvoli, Francesca; Cominelli, Eleonora; Camilli, Emanuela; Ferrari, Marika; Le Donne, Cinzia; Marconi, Stefania; Lisciani, Silvia; Losa, Alessia; et al. (Frontiers in Plant Science, 2023)
Proteases, including serine proteases, are involved in the entire life cycle of plants. Proteases are controlled by protease inhibitors (PI) to limit any uncontrolled or harmful protease activity. The role of PIs in biotic and abiotic stress tolerance is well documented, however their role in various other plant processes has not been fully elucidated. Seed development is one such area that lack detailed work on the function of PIs despite the fact that this is a key process in the life cycle of the plant. Serine protease inhibitors (SPI) such as the Bowman-Birk inhibitors and Kunitz-type inhibitors, are abundant in legume seeds and act as antinutrients in humans and animals. Their role in seed development is not fully understood and present an interesting research target. Whether lowering the levels and activity of PIs, in order to lower the antinutrient levels in seed will affect the development of viable seed, remains an important question. Studies on the function of SPI in seed development are therefore required. In this Perspective paper, we provide an overview on the current knowledge of seed storage proteins, their degradation as well as on the serine protease-SPI system in seeds and what is known about the consequences when this system is modified. We discuss areas that require investigation. This includes the identification of seed specific SPIs; screening of germplasms, to identify plants with low seed inhibitor content, establishing serine protease-SPI ratios and lastly a focus on molecular techniques that can be used to modify seed SPI activity.